Concept of substrate protecting in the fermentative catalysis: mathematical model - Prylutskyy, Yu.I; Borysko, P.O. (Biophysical Bulletin, 2005)
The concept of substrate protecting in fermentative catalysis is mathematically substantiated. Depending on the protecting parameter value the kinetic dependences of the concentration of the chemical reaction product are calculated, which as a whole qualitatively reflects well its phase of growth, and further output to the steady-state (the saturation). The obtained theoretical results can be of interest both with the concrete analysis of experiments from the substrate protecting in the fermentative catalysis and during the study of the action of the ATP as a protector relative to the ATPase activity of myosin in the process of muscle contraction.